Efficacy of protocol‐based pharmacotherapy management on anticoagulation with warfarin for patients with cardiovascular surgery. (15th May 2017) - Katada, Y.; Nakagawa, S.; Minakata, K.; Odaka, M.; Taue, H.; Sato, Y.; Yonezawa, A.; Kayano, Y.; Yano, I.; Nakatsu, T.; Sakamoto, K.; Uehara, K.; et al.
Summary: What is known and objective: Anticoagulation therapy with warfarin requires periodic monitoring of prothrombin time‐international normalized ratio (PT‐INR) and adequate dose adjustments based on the data to minimize the risk of bleeding and thromboembolic events. In our hospital, we have developed protocol‐based pharmaceutical care, which we called protocol‐based pharmacotherapy management (PBPM), for warfarin therapy. The protocol requires pharmacists to manage timing of blood sampling for measuring PT‐INR and warfarin dosage determination based on an algorithm. This study evaluated the efficacy of PBPM in warfarin therapy by comparing to conventional pharmaceutical care. METHODS: From October 2013 to June 2015, a total of 134 hospitalized patients who underwent cardiovascular surgeries received post‐operative warfarin therapy. The early series of patients received warfarin therapy as the conventional care (control group, n=77), whereas the latter received warfarin therapy based on the PBPM (PBPM group, n=68). These patients formed the cohort of the present study and were retrospectively analysed. RESULTS: The indications for warfarin included aortic valve replacement (n=56), mitral valve replacement (n=4), mitral valve plasty (n=22) and atrial fibrillation (n=29). There were no differences in patients' characteristics between both groups. The percentage time in therapeutic range in the first 10 days was significantly higher in the PBPM group (47.1%) than that in the control group (34.4%, P <.005). The average time to reach the steady state was significantly ( P <.005) shorter in the PBPM group compared to the control group (7.3 vs 8.6 days). What is new and conclusion: Warfarin therapy based on our novel PBPM was clinically safe and resulted in significantly better anticoagulation control compared to conventional care. Abstract : A protocol‐based pharmacotherapy management (PBPM) for warfarin therapy after cardiovascular surgery was developed. Warfarin therapy based on our PBPM was clinically safe and resulted in significantly better anticoagulation control compared to conventional care.